Key functions of business - Hayward, Nick; Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2005)
Using Holden as a case study, this program looks at the key functions performed in business on a daily basis. In particular, the program looks at the manufacturing operations, human resources, marketing, sales and finance departments
Title from title screen
Executive producer: Mark McAuliffe
DVD format
Keywords: Holden Ltd; Business -- Case studies; Industrial management -- Case studies; Industrial organization -- Case studies